Wafer grinding protective adhesive film and preparation method thereof

By using the improved thermoplastic layer and antistatic layer in the adhesive film, the problem of different adhesion of the thermoplastic resin layer under different plate temperature conditions is solved, effective protection of the wafer and easy peeling of the adhesive film are achieved, and the quality and reliability of the lamination and grinding process are improved.

CN119684918AInactive Publication Date: 2025-03-25北京钰芯科技有限公司

Patent Information

Application Number
CN202411854217.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the adhesion effect of the thermoplastic resin layer and the wafer bumps varies significantly under different plate temperature conditions, resulting in a decrease in adhesion between the tape and the wafer during the lamination process and a deviation in the total thickness change (TTV) and affecting the product quality of the grinding process.

Method used

An improved thermoplastic layer, an ethylene-vinyl acetate copolymer containing 28% to 35% by weight of vinyl acetate, was used, and an antistatic layer and a primer layer were added to the base layer to improve the performance and reliability of the adhesive film.

Benefits of technology

By controlling the composition and thickness of the thermoplastic layer, effective protection of the wafer in the lamination process is achieved, avoiding the infiltration of grinding fly chips and liquids, and easily peeling off the adhesive film after UV irradiation to avoid glue residue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684918A_ABST
    Figure CN119684918A_ABST
Patent Text Reader

Abstract

The invention provides an adhesive film for wafer grinding protection and a preparation method, and belongs to the field of adhesive films. The adhesive film comprises a base layer and a UV viscosity-reducing adhesive layer, the base layer comprises a heat-resistant layer and a thermoplastic layer, the thermoplastic layer contains an ethylene-vinyl acetate copolymer, and the ethylene-vinyl acetate copolymer contains 28 wt%-35 wt% of vinyl acetate. The adhesive film has excellent performance, can protect a circuit structure of a wafer and avoid penetration of grinding flying chips and grinding liquid during wafer grinding, and is particularly suitable for a bump wafer grinding process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of adhesive films, and in particular relates to a wafer grinding protection adhesive film and a preparation method thereof. Background Art

[0002] Bumping wafers go through lamination and grinding processes before cutting. The lamination process is a pretreatment process for grinding the back of the wafer. When grinding the back of the wafer, an adhesive film is attached to the wafer to protect the front of the wafer from physical impact due to grinding, and to prevent the circuit structure from contacting the dust generated after grinding. After the lamination process, the adhesive film must be removed without damaging the wafer. However, if the adhesive strength of the film is too large, it is difficult to peel off from the wafer. Therefore, in the prior art, a film or tape with a UV (ultraviolet) debonding layer is often used. The film or tape with a UV debonding adhesive layer has a high adhesive strength before UV irradiation and is firmly bonded to the wafer, providing excellent wafer retention. After UV irradiation, the film or tape becomes hard and the adhesive strength is reduced, making it easy to peel off.

[0003] During the lamination process with the wafer, the thermoplastic layer is melted by the plate temperature and pressure of the laminating equipment, and bonded to the bump wafer to protect the bumps on the wafer surface during the wafer grinding process. Under different plate temperature conditions, there are significant differences in the bonding effect between the thermoplastic resin layer and the wafer bumps. Therefore, precise control of the melting temperature is a key technology to achieve effective melting and bonding. In the prior art, the plate temperature of the lamination process equipment is set to 75°C to achieve melt bonding. High temperature environment may have an impact on the adhesive layer of the tape, including increasing adhesive residue and changing the adhesive performance during UV viscosity reduction. These factors may lead to a decrease in the adhesion between the tape and the wafer during the lamination process, as well as a deviation in the total thickness variation (TTV), which in turn affects the product quality of the grinding process. Therefore, optimizing the composition and melting temperature of the thermoplastic resin layer is crucial to improving the quality and reliability of the lamination process and wafer grinding process. Summary of the invention

[0004] All references mentioned herein are incorporated herein by reference. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. Unless otherwise specified, the techniques used or mentioned herein are standard techniques known to one of ordinary skill in the art.

[0005] The present application provides an adhesive film, the thermoplastic layer of which is improved to have excellent performance. During wafer grinding, the adhesive film can protect the circuit structure of the wafer and prevent the infiltration of grinding chips and grinding fluid, and is particularly suitable for bump wafer grinding processes.

[0006] like Figure 1 As shown, the adhesive film 100 of the present invention includes a base layer 110 and a UV adhesive layer 120, wherein the base layer 110 has a multilayer structure, and the base layer 110 is formed by stacking a heat-resistant layer 112 and a thermoplastic layer 114. Further, an adhesive layer 113 is further included between the heat-resistant layer 112 and the thermoplastic layer 114. Further, the adhesive film 100 also includes an antistatic layer 111, which is located on the back side where the heat-resistant layer 112 contacts the thermoplastic layer 114, and is used to prevent the generation of static electricity from damaging the bump wafer and the designed circuit therein.

[0007] Furthermore, a primer layer 140 is further included between the base layer 110 and the UV viscosity-reducing adhesive layer 120, and the primer layer 140 is used to make the base layer 110 and the UV viscosity-reducing adhesive layer 120 contact more closely. The primer layer 140 can be polyurethane, acrylate or polyimide resin. The thickness of the primer layer 140 can be 0.1 μm to 10 μm, preferably 0.1 to 5 μm, and more preferably 0.1 to 3 μm.

[0008] Furthermore, the present application provides an adhesive film, which includes a base layer and a UV anti-viscosity adhesive layer, the base layer includes a heat-resistant layer and a thermoplastic layer, the thermoplastic layer contains ethylene-vinyl acetate copolymer, and the ethylene-vinyl acetate copolymer contains 28wt% to 35wt% of vinyl acetate.

[0009] Furthermore, the ethylene-vinyl acetate copolymer contains 30 wt % to 32 wt % of vinyl acetate.

[0010] Furthermore, the thickness of the thermoplastic layer is 25 μm to 1000 μm.

[0011] Furthermore, the density of the thermoplastic layer is 800 to 1,000 kg / m 3 .

[0012] Furthermore, the storage modulus G' obtained by measuring the dynamic viscoelasticity of the thermoplastic layer at 25°C is 4.2×10 7 Pa to 5.0×10 7 Pa, the storage modulus G' at 75°C is 0.45×10 7 Pa to 0.62×10 7 Pa. .

[0013] Furthermore, the UV viscosity-reducing adhesive layer contains acrylic polymer or acrylic ester.

[0014] Furthermore, the thickness of the UV anti-viscosity adhesive layer is 5 μm to 100 μm.

[0015] Furthermore, the heat-resistant layer contains polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polypropylene (PP) or polyimide (PI).

[0016] Furthermore, the thickness of the heat-resistant layer is 9 μm to 125 μm.

[0017] Furthermore, the adhesive film described in the present application also includes an antistatic layer, which is composed of one or more of poly(3,4-ethylenedioxythiophene) (PEDOT), indium tin oxide (ITO), nanosilver wires, carbon nanotubes (CNTs) or metal grids.

[0018] The beneficial technical effects of the solution of the present invention are:

[0019] The present invention provides a novel composition and content of a thermoplastic layer, wherein the thermoplastic layer contains ethylene-vinyl acetate copolymer, wherein the ethylene-vinyl acetate copolymer contains 28 wt % to 35 wt % of vinyl acetate.

[0020] The adhesive film containing the thermoplastic layer of the present invention can be applied to wafer grinding tape, and its thermoplastic resin layer plays a key role in the lamination process and grinding process with the bump wafer. In the lamination process of attaching the adhesive film to the wafer, the thermoplastic resin layer is heated and plasticized, and can perfectly wrap and tightly fit the bumps on the wafer, ensuring that while maintaining a certain wafer thickness, the consistency and quality of the wafer are guaranteed by controlling the total thickness variation (TTV). In addition, the thermoplastic layer can effectively absorb the physical impact generated during the back grinding process under high-speed rotation, thereby protecting the wafer from damage. After the back grinding of the wafer is completed, the adhesion of the adhesive film can be significantly reduced by ultraviolet (UV) irradiation treatment, so that the adhesive film can be easily peeled off from the processed wafer without leaving any adhesive residue on the wafer surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic diagram of the structure of each layer of an adhesive film of an exemplary embodiment of the present application, wherein 100 is an adhesive film; 110 is a base layer; 120 is a UV-reducing adhesive layer; 112 is a heat-resistant layer; 114 is a thermoplastic layer; 113 is an adhesive layer; 111 is an antistatic layer; and 140 is a primer layer.

[0022] Figure 2 is a photograph of a wafer after being bonded with an adhesive film in an exemplary embodiment of the present application;

[0023] Figure 3 This is a schematic diagram of different locations of a wafer in an exemplary embodiment of the present application. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, these embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. In case of conflict, the present specification shall take precedence.

[0026] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or obtained by existing methods. The methods and examples are for illustrative purposes only and are not intended to be limiting.

[0027] Example 1: Preparation of thermoplastic layers of different components

[0028] The thermoplastic layer (114) of the present application is made of ethylene-vinyl acetate copolymer, and the ethylene-vinyl acetate copolymer contains vinyl acetate (VA), polyethylene (PE), and polypropylene (PP). The composition ratio of the components is shown in Table 1 below. The thickness of the thermoplastic layer (114) of the present application can be 25 to 1,000 μm, 100 to 1,000 μm, 200 to 800 μm, or 100 to 500 μm. Within the above range, the wafer can be effectively protected from physical impact during the grinding process.

[0029] Table 1: Thermoplastic layers with different component contents

[0030] Components (wt%) VA PE PP Experimental Group 1 5 85 10 Experimental Group 2 15 75 10 Experimental Group 3 23 70 7 Experimental Group 4 28 65 7 Experimental Group 5 30 63 7 Experimental Group 6 32 61 7 Experimental Group 7 35 60 5 Experimental Group 8 37 58 5

[0031] Example 2: Preparation of adhesive film

[0032] After drying one side of a 50 μm thick polyethylene terephthalate (PET) film (SH-86, SKC), a polyurethane adhesive (Unithane D-650A, Union Hwaseong) was wet-coated to a thickness of 1 μm and dried, and then bonded to the 350 μm thick thermoplastic layer (TPO350, KM, density 920 kg / m3, ethylene-vinyl acetate copolymer) in Example 1. Next, a PEDOT-based antistatic agent (SH-51B, Suyang Chemtech / CM-107, CM Solution) was wet-coated to a thickness of 1 μm on the other side of the PET film and dried to form an antistatic layer.

[0033] Next, 100 parts by weight of the UV debonding adhesive composition, 0.5 parts by weight of a polyisocyanate crosslinker (AK-75, Aekyung Chemical), 2 parts by weight of a short-wavelength photoinitiator (Ciba Chemical, I-184) and 2 parts by weight of a long-wavelength photoinitiator (Ciba Chemical, I-819) were mixed and stirred to prepare a mixture, and wet-coated on one side of the thermoplastic layer to a thickness of 100 μm. Then, it was dried at 110°C for 3 minutes, and a release layer (XD5BR, Toray Advanced Materials) was attached to prepare an adhesive film. At this time, the thickness of the UV debonding adhesive layer formed by drying the UV debonding adhesive composition was 40 μm.

[0034] Example 3: Performance test of adhesive films containing different thermoplastic layers

[0035] The adhesive films containing the thermoplastic layers of experimental groups 1-8 were subjected to the following performance tests:

[0036] (1) Peel strength test before and after UV irradiation

[0037] According to the Korean standard KS T1028 peeling force measurement method, the adhesive film manufactured in the above experimental group was tested for peeling force with bump wafers before and after UV irradiation. The results are shown in Table 4. When the vinyl acetate content is 28wt%-35wt%, for wafer bumps with a height of 100-250μm, the peeling force is between 800-1000gf / 25mm before UV irradiation; after UV irradiation, the peeling force drops to between 20-30gf / 25mm. Before UV irradiation, it has the best adhesion to protect the bump circuit; after UV irradiation, it has the best peeling effect with less adhesive residue.

[0038] (2) Evaluation of warping and lamination after lamination process

[0039] In order to evaluate the adhesion between the adhesive film, the thermoplastic layer and the wafer manufactured in the above embodiment after the lamination process, the following test was performed, and the specific results are shown in Table 4.

[0040] (2-1) Visual evaluation: In a semiconductor wafer lamination equipment (CUWLS-120, CUON Solution, Korea), the wafer fixing temperature was 60 to 80°C, the lamination roller temperature was 60 to 80°C, and the lamination pressure was 0.50 to 0.55 kg / cm 2 ,After lamination, the bonding state of the wafer and the adhesive film was evaluated with the naked eye.

[0041] Ⅹ: refers to the adhesive film not being attached to the wafer;

[0042] △: refers to the adhesive film only partially attached to the wafer;

[0043] ○: The adhesive film has been attached to the wafer, but there are defects such as bubbles;

[0044] ◎: Indicates that the adhesive film and the wafer are in close contact and no protrusions are visible.

[0045] (2-2) Microscopic evaluation: The bonding state of the bump and the adhesive film (particularly the thermoplastic layer) was examined using an electron microscope (IT PLUS, SOMETECH).

[0046] Ⅹ: refers to the fact that the thermoplastic layer of the adhesive film is not in close contact with the bumps of the wafer;

[0047] △: refers to the thermoplastic layer of the adhesive film only partially contacting the bumps of the wafer;

[0048] ○: refers to the situation where the thermoplastic layer of the adhesive film is already tightly attached to the bump of the wafer, but is not completely tightly attached to the bump and is defective;

[0049] ◎: It means that the thermoplastic layer of the adhesive film is completely bonded to the bumps of the wafer.

[0050] (3) Evaluation of wafer lapping process

[0051] The adhesive films prepared in the above examples were randomly selected and evaluated as follows.

[0052] (3-1) Evaluation of whether the wafer warps during the grinding process: The DFG8760 grinding equipment (DISCO) was used to grind at a speed of 5,000 rpm. The results showed that the adhesive films containing thermoplastic layers in experimental groups 4 to 7 had no protrusions or poor adhesion during the grinding process, among which experimental groups 5 and 6 had the best results. The adhesive films containing thermoplastic layers in the remaining experimental groups had defects such as wafer cracking during the grinding process due to poor warping or poor adhesion after the lamination process.

[0053] (4) Evaluation of glue residue after grinding process

[0054] After back grinding using the adhesive film of the present application, the back grinding wafer was subjected to 1,000 mJ / cm 2 The adhesive film on the wafer was removed on a tape remover (CUWMM-120, CUON) at a wafer fixing temperature of 75°C by ultraviolet irradiation, and the surface condition of the wafer was examined using an electron microscope (ITPLUS, SOMETECH) at ×120 magnification.

[0055] in:

[0056] Ⅹ: refers to the adhesive film not peeling off or only partially peeling off;

[0057] △: The chip is damaged and / or there is residue on the wafer surface;

[0058] ○: The chip is not damaged, but there is glue on the surface of the wafer;

[0059] ◎: The chip is not damaged, the wafer surface is clean, and there is no glue residue.

[0060] The evaluation results are shown in Table 4. After the adhesive films containing the thermoplastic layers of the experimental groups 4-6 were used for wafer grinding, the chips were not damaged, the wafer surface was clean, and there was no adhesive residue. Figure 2 This is a photograph of the wafer surface after being polished using the adhesive film containing the thermoplastic layer of Experimental Group 6 of the present application.

[0061] (5) Wafer thickness deviation measurement after grinding (flatness measurement)

[0062] In this evaluation example, the maximum thickness deviation of 9 points of the wafer with a bump height of 200-250μm after grinding with the adhesive film corresponding to the experimental groups 3-7 is counted, including 5 points T, C, B, L, R (top / center / bottom / left / right) of the backside grinding wafer and 4 points between each point, as shown in detail. Figure 3 Measure and obtain the total thickness value (TTV, μm).

[0063] Before lamination processing, that is, before wafer grinding, the measured thickness at different locations is shown in Table 2 below.

[0064] Table 2: Wafer thickness measurements before grinding

[0065]

[0066]

[0067] After back grinding using the adhesive film of the embodiment of the present application, the measurement data of different sites of different wafers are shown in Table 3 below.

[0068] Table 3: Thickness measurements after wafer grinding

[0069] Location Wafer 01(μm) Wafer 02(μm) Wafer 03(μm) Wafer 04(μm) Wafer 05(μm) C 832.4 831.0 828.5 829.0 828.9 CL 831.8 830.2 828.3 828.4 831.9 L 832.4 831.6 826.8 828.2 830.0 CR 832.5 829.6 826.8 828.0 830.4 R 832.6 830.3 827.2 828.1 830.9 TC 832.9 830.4 827.7 827.6 830.3 T 834.8 830.6 827.0 827.0 831.4 BC 832.0 830.2 827.6 828.9 830.2 B 832.3 831.0 828.1 829.5 828.7 Min 831.8 829.6 826.8 827.0 828.7 Max 834.8 831.6 828.5 829.5 831.9 TTV 3.0 2.0 1.7 2.5 3.2

[0070] (6) Energy storage mode evaluation

[0071] For the thermoplastic layer of experimental groups 1-8, samples with a radius of 8 mm and a thickness of 1 mm were prepared, and then the storage elastic modulus thereof at 20° C. to 80° C. was measured using a dynamic viscoelasticity tester (Rheometrics, RMS-800). The measurement frequency was 1 Hz and the strain was 0.1 to 3%. The results are shown in Table 4.

[0072] The performance test results of this embodiment are shown in Table 4 below:

[0073]

[0074]

[0075] In summary, when the thermoplastic layer made of ethylene-vinyl acetate copolymer contains 28wt% to 35wt% of vinyl acetate, the adhesive film containing the thermoplastic layer is plasticized during the lamination process with the bump wafer (the process of attaching the adhesive film to the wafer), and can perfectly wrap the protruding bumps on the wafer and fit tightly, so that while maintaining a certain wafer thickness (the wafer will not be excessively thickened), it can be highly fitted with the bump wafer. In addition, even if the bump wafer with the adhesive film is back-ground while rotating at high speed, the physical impact during grinding will be absorbed by the thermoplastic layer, thereby protecting the chip without damaging the wafer. In addition, since UV can be irradiated after back grinding to reduce the adhesion of the adhesive film, the adhesive film can be easily peeled off from the wafer without leaving any glue residue.

Claims

1. An adhesive film comprising a base layer and a UV-reducing adhesive layer, wherein the base layer comprises a heat-resistant layer and a thermoplastic layer, and the thermoplastic layer contains ethylene-vinyl acetate copolymer, characterized in that: The ethylene-vinyl acetate copolymer includes 28 wt % to 35 wt % of vinyl acetate.

2. The adhesive film according to claim 1, characterized in that The ethylene-vinyl acetate copolymer contains 30 wt % to 32 wt % of vinyl acetate. 3 . The adhesive film according to claim 1 , wherein the thermoplastic layer has a thickness of 25 μm to 1000 μm.

4. The adhesive film according to claim 3, wherein the density of the thermoplastic layer is 800 to 1,000 kg / m 3 .

5. The adhesive film according to claim 1, wherein the storage modulus G' of the thermoplastic layer at 25°C is 4.2×10 7 Pa to 5.0×10 7 Pa, the storage modulus G' at 75°C is 0.45×10 7 Pa to 0.62×10 7 Pa.

6. The adhesive film according to claim 1, wherein the UV-reducing adhesive layer contains acrylic polymer or acrylic ester. 7 . The adhesive film according to claim 6 , wherein the thickness of the UV adhesive layer is 5 μm to 100 μm. 8 . The adhesive film according to claim 1 , wherein the heat-resistant layer comprises polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polypropylene (PP) or polyimide (PI). 9 . The adhesive film according to claim 8 , wherein the heat-resistant layer has a thickness of 9 μm to 125 μm.

10. The method according to claim 1, wherein the adhesive film further comprises an antistatic layer, wherein the antistatic layer is composed of one or more of poly(3,4-ethylenedioxythiophene) (PEDOT), indium tin oxide (ITO), nano silver wires, carbon nanotubes (CNTs) or metal grids.

Citation Information

Patent Citations

  • Wafer cutting protective film

    CN118931404A

  • Adhesive film for protecting semiconductor wafer and preparation method thereof

    KR102099071B1

  • Adhesion film for wafer back grinding and its manufacturing method

    KR102411362B1

Cited By

  • Thermosetting liquid phase composition capable of being used as back grinding protective layer of semiconductor substrate and application of thermosetting liquid phase composition

    CN120158157A